2020
DOI: 10.22271/j.ento.2020.v8.i5u.7709
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Amycoida and Astioida (Arachnida: Araneae: Salticidae: Salticinae) in India

Abstract: A total of 56 species under 14 genera were recorded in most of the states and union territories of India except Himachal Pradesh, Jharkhand, Chattisgarh, Sikkim, Meghalaya, Daman & Du and Dadra & Nagar Haveli, and Lakshadweep. Out of them, 27 species are endemic. The Amycoida is represented by only 2 species of a single genus (tribe Sitticini), one from Ladakh (Attulus avocator) and one from Jammu & Kashmir (Attulus diductus). Maximum number of species of these spiders were recorded from Kerala (25 species) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 37 publications
(76 reference statements)
0
8
0
1
Order By: Relevance
“…(2022) also obtained significant results of Flonicamid against adults of Bemisia tabaci. Flonicamid gave satisfactory control of whitefly on okra (Singh et al, 2020). Afzal et al (2014) in an experiment found significant mortality of Bemisia tabaci adults by using Diafenthiuron.…”
Section: Resultsmentioning
confidence: 97%
“…(2022) also obtained significant results of Flonicamid against adults of Bemisia tabaci. Flonicamid gave satisfactory control of whitefly on okra (Singh et al, 2020). Afzal et al (2014) in an experiment found significant mortality of Bemisia tabaci adults by using Diafenthiuron.…”
Section: Resultsmentioning
confidence: 97%
“…Several studies have reported worsening blood profiles due to stress [35,37]. Immune markers TNF-α and IL-6 are decreased under stress.…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…Vitellogenin is a precursor protein of egg yolk; however, it is also known that vitellogenin acts as an antioxidant that promotes longevity in queen bees -they have a higher expression of the vitellogenin gene compared to workers and are more resistant to oxidative stress [17]. It is also was discovered to be influencing the immune system [18]. In birds, active synthesis of vitellogenin is a marker of the reproductive period.…”
Section: Searching For Possible Systemic Regulatorsmentioning
confidence: 99%